Seismotectonic models and CN algorithm : the case of Italy - Panza, Giuliano Francesco; Rotwain, Irina M.; Costa, Giovanni; Orozova-Stanishkova, Ivanka (Trieste : International Centre for Theoretical Physics, 1995)
08